Insulin use, adipokine profiles and breast cancer prognosis. (January 2017) - Wintrob, Zachary A.P.; Hammel, Jeffrey P.; Khoury, Thaer; Nimako, George K.; Fu, Hsin-Wei; Fayazi, Zahra S.; Gaile, Dan P.; Forrest, Alan; Ceacareanu, Alice C.
Highlights: Insulin and insulin secretagogue users have poorer breast cancer (BC) outcomes. Estrogen receptor negative BC occurs more among insulin and secretagogues users. Insulin users have lower baseline C-peptide and elevated leptin, IL-6, TNF-α and CRP. C-peptide is inversely correlated with IL-1β and IL-1Ra among insulin users. IL-1β and adiponectin levels are directly correlated in insulin users only. Abstract: Background: Type-2 diabetes mellitus (T2DM) and breast cancer (BC) share common cytokine signaling changes resultant from adipose tissue dysfunction. This modified adipokine signaling was shown to be directly associated with changes in the body mass index (BMI) and diet and it is expected to also be influenced by T2DM pharmacotherapy. We evaluated the relationship between pre-existing diabetes treatment, circulating adipokine levels at cancer diagnosis, and long-term outcomes. Methods: All incident BC cases were reviewed (01/01/2003-12/31/2009, N = 2194). Each of the subjects with baseline T2DM (cases) was matched with two other subjects without T2DM (controls) based on the following criteria: age, BMI, ethnicity, menopausal status and tumor stage. All cases and controls with available baseline plasma and tumor biopsies, and being surgery and BC treatment naïve, were included (N1  = 97, N2  = 194). Clinical history and vital status were documented. Adipokine levels (adiponectin, leptin, TNF-α, CRP, IL-1β, IL-1Ra, IL-6, and C-peptide) were assessed by either ELISA or Luminex® assays. Cancer outcomes were assessed by Kaplan-Meier analysis; associations between categorical variables were assessed by Fisher's exact test, categorical and continuous variables by Kruskal-Wallis or Wilcoxon Rank-Sum test, where appropriate. Multivariate adjustments (MVP, multivariate p-value) were performed accounting for age, tumor stage, BMI, estrogen receptor (ER) status and cumulative comorbidity. All biomarker correlations were assessed by the Pearson method. Utilization of insulin and insulin secretagogues was associated with ER (−) phenotype (p = 0.008, p = 0.043) and poorer BC outcomes (p = 0.012, p = 0.033). Insulin users were found to have lower C-peptide and higher IL-6, TNF-α and CRP levels, of which elevated CRP and TNF-α were associated with poorer BC outcomes (p = 0.003, MVP = 0.210). Insulin remarked by higher leptin levels as compared to controls (p = 0.052), but did not differ significantly from non-users. Although lower adiponectin levels were observed among non-insulin users as compared to controls (p < 0.001, MVP = 0.006), insulin use seemed to have restored adiponectin production. C-peptide levels were lower among insulin users as compared to non-users (p < 0.001, MVP < 0.001) and approached levels comparable with those of the controls. In the overall dataset, C-peptide lower than 0.75 ng/ml were strongly associated with poorer survival (p = 0.007, MVP = 0.002). Among insulin users, C-peptide levels were inversely correlated with IL-1β and IL-1Ra levels only after full adjustment (p = 0.012, p = 0.030); the correlation was unremarkable in other groups. Conclusion: Insulin use is associated with elevated leptin, CRP, TNFα, and lower C-peptide and also linked to poor BC outcomes. More research is needed to verify these findings; however, we are among the first to correlate pharmacotherapy use, measures of adipose tissue dysfunction and cancer outcomes.